Reverse ink system based on positive photosensitive mechanism and application thereof

By using a reversal ink system based on positive photosensitive mechanism, and utilizing azide photosensitizers and phenolic epoxy resin hydrogen bond networks, combined with multifunctional epoxy-acrylic hybrid resins and light scattering materials, the problems of crosslinking density differences and insufficient reflectivity of traditional inks in high-precision applications are solved. This results in improved high reflectivity, hue stability and heat resistance, making it suitable for high-density PCB manufacturing of miniLED/microLED display technologies.

CN121006098APending Publication Date: 2025-11-25FUZHOU MINWEI CIRCUIT BOARD CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511131829.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-13
Publication Date
2025-11-25

AI Technical Summary

Technical Problem

Traditional negative photosensitive inks are easily affected by uneven superposition of light scanning energy in high-precision applications, resulting in differences in cross-linking density, forming bright and dark stripes or color differences in splicing. In addition, they have insufficient reflectivity, high yellowing index, limited resolution, and insufficient heat resistance, making it difficult to meet the high-density PCB manufacturing requirements of miniLED/microLED display technology.

Method used

The reverse ink system, based on the positive photosensitive mechanism, utilizes an azide photosensitizer to decompose under UV light to form a hydrophilic exposure zone. This is combined with a phenolic epoxy resin hydrogen bond network and a multifunctional epoxy-acrylic hybrid resin to improve the developer penetration and crosslinking density. Silica microspheres and zirconium oxide particles are added for light scattering to enhance reflectivity and interfacial adhesion. The green ink uses a blend of phthalocyanine green G and titanium yellow to adjust the hue.

Benefits of technology

It eliminates light and dark stripes and color differences at the seams, significantly improves reflectivity and hue stability, enhances resolution and heat resistance, and improves the processing performance and lifespan of inks on high-density PCBs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a reverse printing ink system based on a positive photosensitive mechanism and application thereof. The printing ink system comprises three types of products, namely black matte printing ink, high-reflectivity white printing ink and green printing ink, the production process of the ink system comprises the following steps: 1) synthesizing the film-forming resin; (2) sharing the film-forming resin with a pigment system, a dispersion medium and a functional additive; and 3) applying the reverse ink system to PCB manufacturing. According to the method, the characteristic of'dissolution in an exposure area 'is realized through positive light sensing, and the problems of scanning splicing printing, color difference and insufficient reflectivity in a traditional solder mask process are solved by matching with a special developing solution and a DI exposure light spot shaping technology; compared with the prior art, the reverse printing ink system has the advantages that the yellowing index, the resolution ratio, the heat resistance and the like are remarkably improved, and the reverse printing ink system is suitable for manufacturing a high-end mini LED / micro LED PCB (Printed Circuit Board).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of printed circuit board (PCB) manufacturing technology, and in particular to a reversing ink system based on positive photosensitive mechanism and its application. Background Technology

[0002] In the field of printed circuit board (PCB) manufacturing, especially driven by the rapid development of high-density miniLED / microLED display technology, the solder resist process has placed higher demands on the performance of inks.

[0003] Traditional solder resist inks mostly use negative photosensitive mechanisms, relying on cross-linking curing of the exposed area to achieve pattern formation. However, this technology has gradually revealed significant defects in high-precision applications. The curing process of negative inks is easily affected by uneven superposition of light scanning energy, resulting in local cross-linking density differences, forming bright and dark stripes or splicing color differences, which seriously affect the optical consistency of the display panel.

[0004] Secondly, traditional white ink has insufficient reflectivity, mainly due to uneven pigment dispersion and light absorption loss by the resin matrix, which cannot meet the high brightness reflection requirements of miniLED backlight; while black ink faces problems such as excessively high surface reflectivity and poor stability of matte effect, which easily causes glare interference.

[0005] In addition, existing ink systems generally suffer from problems such as high yellowing index (Δb*>3), resolution limited to above 50μm, and insufficient heat resistance, making it difficult to meet the requirements of fine circuit processing and long-term reliability of high-density PCBs.

[0006] The development process of traditional inks relies on cross-linking to inhibit dissolution. Uneven curing depth of the film-forming resin can lead to rough edges of the pattern. Furthermore, the weak bonding between the resin and pigment interface makes it prone to delamination and peeling under thermal stress.

[0007] These technological bottlenecks limit the breakthroughs in PCBs towards higher integration, better optical performance, and longer lifespan, necessitating the development of new photosensitive ink systems to address these pain points. Summary of the Invention

[0008] The purpose of this invention is to address the shortcomings of existing technologies by proposing a reversal ink system based on positive photosensitive mechanism and its application.

[0009] To achieve the above objectives, the present invention adopts the following technical solution:

[0010] This invention first proposes a reversal ink system based on positive photosensitive mechanism, which is a high-reflectivity white oil made from the following raw materials in parts by weight:

[0011] Film-forming resin: 50-55 parts of epoxy-modified acrylic resin;

[0012] Photosensitive system: 10-12 parts of azidolated polyester;

[0013] Pigment system: 30-35 parts rutile TiO2, 3-5 parts zirconium oxide brightener;

[0014] Dispersion medium: 25-35 parts of diethylene glycol butyl ether acetate;

[0015] Functional additives: 0.5-1 parts of ultraviolet absorber, 2-3 parts of silica microspheres;

[0016] The preparation process of the epoxy-modified acrylic resin includes the following steps:

[0017] 1) Synthesis of prepolymer solution

[0018] Add propylene glycol methyl ether acetate solvent to the reactor, purge with nitrogen to replace oxygen, heat to 80°C, and start stirring at 100 rpm.

[0019] A monomer mixture was obtained by mixing methyl methacrylate, acrylic acid, phosphate monomer, hydroxyethyl acrylate, and 2-hydroxy-4-(3-methacryloyloxypropoxy)benzophenone.

[0020] Azobisisobutyronitrile (AIBN) was dissolved in propylene glycol methyl ether acetate to obtain an AIBN solution.

[0021] Slowly add monomer mixture and AIBN solution to the reactor, keep warm at 80°C for 2 hours, add more AIBN solution, cool to 70°C to obtain prepolymer solution;

[0022]

[0023] 2) Epoxy ring-opening grafting

[0024] Add bis((3,4-epoxycyclohexyl)methyl)adipate, triphenylphosphine, and phenyl glycidyl ether, heat to 85±1℃, adjust the stirring speed to 80rpm, react for 4h, cool to 60℃, add propylene glycol methyl ether acetate to dilute, terminate the reaction, and obtain the crude product of epoxy-modified acrylic resin.

[0025]

[0026] Methyl methacrylate, acrylic acid, phosphate monomers, hydroxyethyl acrylate, and benzophenone monomers containing UV-absorbing groups are copolymerized under AIBN initiation to generate a prepolymer. The carboxyl / hydroxyl groups of the prepolymer are ring-opened and grafted with the epoxy groups of bis((3,4-epoxycyclohexyl)methyl)adipate under phosphine catalysis to form an epoxy-acrylic acid block structure. Phenyl glycidyl ether is used as a monofunctional epoxy diluent to control the crosslinking density.

[0027] 3) Post-processing

[0028] Add antioxidants, stir at 60℃ for 40 min until completely dissolved, remove volatile monomers under -0.09MPa vacuum at 80℃, and stop stirring when the distillate is <0.5kg / h;

[0029] After cooling to 40℃ and filtering through a 5μm filter bag, a slightly yellow, transparent, viscous liquid with a solid content of 60±2% is obtained, which is epoxy-modified acrylic resin.

[0030] Preferably, the ultraviolet absorber is a benzotriazole ultraviolet absorber; the zirconium oxide brightener has particle sizes of 0.2 μm and 1 μm, and the mass ratio of the two particle sizes is 1:1.

[0031] Preferably, in step 1), the mass ratio of methyl methacrylate, acrylic acid, phosphate monomer, hydroxyethyl acrylate, and 2-hydroxy-4-(3-methacryloyloxypropoxy)benzophenone is 46:4.5:1.8:18:2.7.

[0032] The mass ratio of monomer mixture, bis((3,4-epoxycyclohexyl)methyl)adipate, triphenylphosphine, and phenyl glycidyl ether is 73:15:0.15:5; the amount of azobisisobutyronitrile is 1% of the mass of monomer mixture.

[0033] In step 2), the propylene glycol methyl ether acetate used for dilution is 20% of the total amount of reactants;

[0034] In step 3), the antioxidant is antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1, and the amount used is 1% of the mass of the epoxy-modified acrylic resin crude product.

[0035] This invention proposes a reversal ink system based on positive photosensitive mechanism, which is made into a black matte ink from the following raw materials in parts by weight:

[0036] Film-forming resin: 45-50 parts of multifunctional epoxy-acrylic hybrid resin;

[0037] Photosensitizing system: 8-10 parts of o-naphthoquinone diazidesulfonate;

[0038] Pigment system: 25-30 parts nano carbon black, 5-8 parts silica matting agent;

[0039] Dispersion medium: a mixture of 25-35 parts of propylene glycol methyl ether acetate and cyclohexanone in a volume ratio of 7:3;

[0040] Functional additives: 0.1-0.3 parts of fluorocarbon leveling agent, 0.5-1 parts of silane coupling agent;

[0041] The preparation process of the multifunctional epoxy-acrylic hybrid resin includes the following steps:

[0042] ① Synthesis of crude resin products

[0043] Add bisphenol A epoxy resin and propylene glycol methyl ether acetate to the reactor, heat to 90°C, and stir at 150 rpm to dissolve.

[0044] Hydroxyethyl acrylate and triethylamine were added dropwise at a flow rate of 1.5 L / h and reacted at 90 ± 2 °C for 3 h.

[0045] Cool to 70℃, add octadecyl methacrylate, methacryloxyethyltrimethylammonium chloride, chain transfer agent, and propylene glycol methyl ether acetate. Purge with nitrogen for 30 minutes to remove oxygen. Prepare a solution of azobisisobutyronitrile and propylene glycol methyl ether acetate and add it to the reaction vessel. Heat to 80℃ and react for 4 hours to obtain crude resin product.

[0046] ② Post-treatment after anhydride end-capping

[0047] KH-570 was added to the crude resin product, and the temperature was raised to 100℃ and reacted for 2 hours; the temperature was lowered to 60℃, and succinic anhydride was added and reacted for 5 hours.

[0048] The resin was cooled to 40°C, degassed under vacuum at -0.08 MPa for 30 min, and filtered through a 5 μm filter bag to obtain a multifunctional epoxy-acrylic hybrid resin.

[0049] Bisphenol A epoxy resin reacts with hydroxyethyl acrylate, undergoing ring-opening esterification of the epoxy groups to introduce acrylic double bonds, followed by free radical polymerization:

[0050]

[0051] Subsequently, anhydride is used to cap the solution to increase the penetration of the developer.

[0052] Preferably, in ①, the mass ratio of bisphenol A epoxy resin, hydroxyethyl acrylate, triethylamine, octadecyl methacrylate, methacryloxyethyltrimethylammonium chloride, chain transfer agent, and azobisisobutyronitrile is 20:8:0.1:7:4:0.3:0.2;

[0053] In step ②, the amount of KH-570 is 10% of the mass of the crude resin product; the amount of succinic anhydride is 10% of the mass of the crude resin product; propylene glycol methyl ether acetate is used as a solvent, and by adjusting the amount of propylene glycol methyl ether acetate added, the solid content of the multifunctional epoxy-acrylic hybrid resin is 70±2%.

[0054] This invention proposes a reversal ink system based on positive photosensitive mechanism, which is made into green ink from the following raw materials in parts by weight:

[0055] 48-52 parts of film-forming resin: multifunctional epoxy-acrylic hybrid resin;

[0056] 9-11 parts of the photosensitizing system: o-naphthoquinone diazidesulfonate;

[0057] A pigment system of 17-21 parts: 15-18 parts Phthalocyanine Green G, 2-3 parts Titanium Yellow;

[0058] 25-35 parts of dispersion medium: propylene glycol methyl ether acetate;

[0059] 0.2-0.4 parts of functional additives: fluorocarbon leveling agent.

[0060] This invention also proposes a method for preparing the reversal ink system based on the positive photosensitive mechanism, comprising the following steps:

[0061] The film-forming resin was mixed with a dispersion system at 40°C and stirred at 500 rpm for 30 min; the pigment system, photosensitizing system and functional additives were added and dispersed at 1200 rpm for 40 min; the fineness was tested using a Hergmann fineness meter, and the fineness was required to be ≤15 μm, thus obtaining the resin mixture;

[0062] The resin mixture was circulated and milled three times in a sand mill until the outlet fineness was ≤5μm; black oil or green oil was obtained; after milling, silica microspheres were added to the resin mixture and dispersed at 600rpm for 20min to obtain white oil;

[0063] The product is obtained by filtering with a 5μm filter bag and then packaging.

[0064] The inverted ink system based on positive photosensitive mechanism proposed in this invention is applied to the solder mask process of high-density PCBs for miniLEDs / microLEDs, and includes the following steps:

[0065] S1, Substrate pretreatment

[0066] Volcanic ash grinding plates, brushing pressure 1.2-1.5 kgf / cm² 2 The etching speed was 1.8 m / min, the wear track overlap rate was 30%; chemical ultra-roughening was performed using a mixed aqueous solution of 100 mL / L H2SO4 and 50 mL / L H2O2, at a temperature of 30 °C for 90 s, with a micro-etching depth of approximately 1.2 μm.

[0067] S2, Coating

[0068] The curtain is coated with matte black ink or green ink, with a slit width of 0.15 mm and a flow rate of 8 mL / min; high-reflectivity white ink is screen-printed using a 36T screen and a squeegee with a hardness of 70° Shore.

[0069] S3, Pre-baking

[0070] Black matte ink or green ink is pre-baked in stages. The first stage is hot air circulation at 70℃ for 5 minutes; the second stage is infrared heating at 80℃ for 10 minutes. High reflectivity white oil is continuously dried in a tunnel oven at 72℃ with a set wind speed of 1.0 m / s for 25 minutes.

[0071] S4, DI exposure

[0072] The surface dose of the substrate was measured using a 365nm / 405nm radiometer. The exposure parameters were set as follows: the exposure wavelength for the high-reflectivity white oil was 405nm, and the dose was 100mJ / cm². 2 Focal length compensation +15μm; exposure wavelength of black matte ink is 365nm, dose is 65mJ / cm. 2 Focal length compensation +10μm; exposure wavelength of green ink is 365nm, dosage is 80mJ / cm. 2 Focal length compensation +12μm;

[0073] Azide-modified polyester / o-naphthoquinone diazidesulfonate (DNQ) decomposes under UV exposure, generating an enone intermediate which is then hydrolyzed into a carboxylic acid (hydrophilic). This causes the exposed area to dissolve in the alkaline developer, while the unexposed area resists the developer due to the hydrophobicity of the photosensitive system.

[0074] S5, Development

[0075] The developing solution was sprayed onto the substrate at 30±0.5℃, with a spraying pressure of 2.0 kgf / cm². 2 The nozzle angle is 30°; the developing point is checked every 30 seconds, and the process is stopped when the ink retention rate in the unexposed area reaches about 50%; after spraying with deionized water, the area is dried with nitrogen at 40°C.

[0076] S6, Post-curing

[0077] The substrate was subjected to step curing, with the program set as follows: heating to 80°C at a heating rate of 5°C / min and curing for 20 min; heating to 100°C at a heating rate of 3°C / min and curing for 30 min; and heating to 150°C at a heating rate of 2°C / min and curing for 60 min.

[0078] At 80℃, the small molecules remaining in the system evaporate; at 100℃, the water in the system evaporates completely; at 150℃, the epoxy ring opens and deeply crosslinks, and the film-forming resin cures.

[0079] After curing, a printed circuit board protected by the reverse ink system is obtained.

[0080] Preferably, the developer is prepared as follows:

[0081] Tetramethylammonium hydroxide, ethylene glycol butyl ether, ammonium polyacrylate, and deionized water were mixed and sonicated for 10 minutes, then filtered to prepare a developing solution containing 1% tetramethylammonium hydroxide, 6% ethylene glycol butyl ether, and 0.5% ammonium polyacrylate by mass.

[0082] In the black and green ink exposure areas, the o-naphthoquinone diazidesulfonate DNQ decomposes into carboxylic acid, allowing the area to dissolve in the alkaline developer; the unexposed areas remain hydrophobic, resisting developer erosion, thus achieving "exposure of the exposure area".

[0083] The photolysis of white ink azidopolyester is similar to the decomposition mechanism of DNQ, decomposing into carboxylic acids under 405nm light, with the same mechanism.

[0084] Compared with the prior art, the beneficial effects of the present invention are:

[0085] Traditional negative inks rely on "cross-linking curing in the exposed area," which leads to color differences due to uneven superposition of light scanning energy and variations in cross-linking density. This invention, however, uses an azide photosensitizer that decomposes into indene carboxylic acid under a 365 / 405nm laser, changing the exposed area from hydrophobic to hydrophilic. This forms a hydrogen bond network with the hydroxyl groups of the phenolic epoxy resin, promoting developer penetration. The development process involves dissolution rather than cross-linking, avoiding bright and dark streaks caused by localized curing differences and fundamentally eliminating color differences at the seams.

[0086] The three inks designed in this invention include a black matte ink with added 1-3μm silica microspheres, forming a micron-level rough structure on the surface; the incident light is captured in the microcavity structure through multiple scattering, significantly reducing reflection and improving haze; the carbon black / resin interface bonding is enhanced by a silane coupling agent, resisting the thermal stress of 288℃ solder and avoiding blistering. The high-reflectivity white oil uses a mixture of 0.2μm and 1μm zirconium oxide particles for dual-scale scattering enhancement. Based on Mie scattering theory, the small particles (0.2μm) efficiently scatter short-wavelength blue light, while the large particles (1μm) scatter long-wavelength red light, synergistically covering the entire visible spectrum and significantly improving reflectivity. The epoxy-modified acrylic resin used increases the resin crosslinking degree through epoxy ring-opening polymerization during the curing stage, eliminating unsaturated bonds and inhibiting film oxidation and yellowing. The green ink uses a 3:1 blend of phthalocyanine green G (strong green light absorption) and titanium yellow (red and yellow light reflection) to counteract the inherent blue light shift tendency of phthalocyanine green, resulting in stable hue. All three inks have made breakthroughs in optical performance compared to traditional inks.

[0087] This invention's film-forming system, through innovative resin design and functional modification, exhibits significant advantages in mechanical strength, interfacial adhesion, development compatibility, and thermal stability. For epoxy-modified acrylic resin, the acrylic backbone constructs a low-polarity environment, reducing light scattering loss. The epoxy grafting sites form hydrogen bonds with the hydroxyl groups on the TiO2 surface, preventing filler agglomeration. The covalent bond of (2-hydroxy-4-(3-methacryloyloxypropoxy)benzophenone) is linked to the resin chain, providing sustained UV absorption and inhibiting yellowing. For the multifunctional epoxy-acrylic hybrid resin, the epoxy segments provide a rigid framework, imparting high hardness and heat resistance to the film. The acrylic side chains introduce long alkyl chains, enhancing flexibility and resisting thermal stress cracking. Quaternary ammonium salt monomers stabilize the pigment system dispersion through electrostatic interaction, preventing coarsening. In practical applications, the film-forming resin will spread uniformly on the PCB substrate, demonstrating excellent processing performance. Detailed Implementation

[0088] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.

[0089] The purity and manufacturers of the various drugs used in the experiment are shown in Table 1.

[0090] Table 1. Raw Material Drug Information

[0091] Hydroxyethyl acrylate Analytical Pure Chizhou Fangda Technology Co., Ltd. 2-Hydroxy-4-(3-methacryloyloxypropoxy)benzophenone Analytical Pure Hubei Xingyan New Material Technology Co., Ltd. Azobisisobutyronitrile Analytical Pure Shandong Yukang Chemical Co., Ltd. bis-(3,4-epoxycyclohexyl)adipate Analytical Pure Hefei Shenghang Pharmaceutical Technology Co., Ltd. Triphenylphosphine Analytical Pure Lianyungang Xuanyuan Chemical Co., Ltd. Phenylated glycidyl ether Analytical Pure Anhui Zesheng Technology Co., Ltd. Antioxidant 1010 Analytical Pure Qingdao Jiebao Auxiliary Agents Co., Ltd. Antioxidant 168 Analytical Pure Changzhou Qingmu Biotechnology Co., Ltd. Nano carbon black Analytical Pure Cabot Mogul L Silica matting agent Analytical Pure Grace SYLOID MX150 Propylene glycol methyl ether acetate Analytical Pure Hefei Tianjian Chemical Co., Ltd. Cyclohexanone Analytical Pure Wuhan Beiguofeng Chemical Co., Ltd. Fluorocarbon leveling agent Analytical Pure DuPont Capstone FS-30 Silane coupling agents Analytical Pure Momentive Silquest A-187 Phthalocyanine Green G Analytical Pure DIC Company Lionol Green 6YK Titanium Yellow Analytical Pure Ishihara TTO-55N Bisphenol A type epoxy resin Analytical Pure Sigma Aldrich (Shanghai) Trading Co., Ltd. Triethylamine Analytical Pure Jiangsu Runfeng Synthetic Technology Co., Ltd. Octadecyl methacrylate Analytical Pure Suzhou Senfida Chemical Co., Ltd. Methacryloxyethyltrimethylammonium chloride Analytical Pure Qingdao Renas Polymer Materials Co., Ltd. Chain transfer agent Analytical Pure Wuxi Zhiyuan Chemicals Co., Ltd. Tetramethylammonium hydroxide Analytical Pure Hubei Xinjiecheng Chemical Technology Co., Ltd. Ethylene glycol butyl ether Analytical Pure Shanghai Demao Chemical Co., Ltd. ammonium polyacrylate Analytical Pure Liyang Ruipu New Materials Co., Ltd.

[0092] Preparation Example 1:

[0093] The preparation process of epoxy-modified acrylic resin includes the following steps:

[0094] 1) Synthesis of prepolymer solution

[0095] Add propylene glycol methyl ether acetate solvent to the reactor, purge with nitrogen to replace oxygen, heat to 80°C, and start stirring at 100 rpm.

[0096] A monomer mixture was obtained by mixing methyl methacrylate, acrylic acid, phosphate monomer, hydroxyethyl acrylate, and 2-hydroxy-4-(3-methacryloyloxypropoxy)benzophenone.

[0097] Azobisisobutyronitrile (AIBN) was dissolved in propylene glycol methyl ether acetate to obtain an AIBN solution.

[0098] Slowly add monomer mixture and AIBN solution to the reactor, keep warm at 80°C for 2 hours, add more AIBN solution, cool to 70°C to obtain prepolymer solution;

[0099] 2) Epoxy ring-opening grafting

[0100] Add bis((3,4-epoxycyclohexyl)methyl)adipate, triphenylphosphine, and phenyl glycidyl ether, heat to 85±1℃, adjust the stirring speed to 80rpm, react for 4h, cool to 60℃, add propylene glycol methyl ether acetate to dilute, terminate the reaction, and obtain the crude product of epoxy-modified acrylic resin.

[0101] 3) Post-processing

[0102] Add antioxidants, stir at 60℃ for 40 min until completely dissolved, remove volatile monomers under -0.09MPa vacuum at 80℃, and stop stirring when the distillate is <0.5kg / h;

[0103] After cooling to 40℃ and filtering through a 5μm filter bag, a slightly yellow, transparent, viscous liquid with a solid content of 60±2% is obtained, which is epoxy-modified acrylic resin.

[0104] In step 1), the mass ratio of methyl methacrylate, acrylic acid, phosphate monomer, hydroxyethyl acrylate, and 2-hydroxy-4-(3-methacryloyloxypropoxy)benzophenone is 46:4.5:1.8:18:2.7.

[0105] The mass ratio of monomer mixture, bis((3,4-epoxycyclohexyl)methyl)adipate, triphenylphosphine, and phenyl glycidyl ether is 73:15:0.15:5; the amount of azobisisobutyronitrile is 1% of the mass of monomer mixture.

[0106] In step 2), the propylene glycol methyl ether acetate used for dilution is 20% of the total amount of reactants;

[0107] In step 3), the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1, and the amount used is 1% of the mass of the epoxy-modified acrylic resin crude product.

[0108] Preparation Example 2

[0109] The preparation process for synthesizing multifunctional epoxy-acrylic hybrid resins includes the following steps:

[0110] ① Synthesis of crude resin products

[0111] Add bisphenol A epoxy resin and propylene glycol methyl ether acetate to the reactor, heat to 90°C, and stir at 150 rpm to dissolve.

[0112] Hydroxyethyl acrylate and triethylamine were added dropwise at a flow rate of 1.5 L / h and reacted at 90 ± 2 °C for 3 h.

[0113] Cool to 70℃, add octadecyl methacrylate, methacryloxyethyltrimethylammonium chloride, chain transfer agent, and propylene glycol methyl ether acetate. Purge with nitrogen for 30 minutes to remove oxygen. Prepare a solution of azobisisobutyronitrile and propylene glycol methyl ether acetate and add it to the reaction vessel. Heat to 80℃ and react for 4 hours to obtain crude resin product.

[0114] ② Post-treatment after anhydride end-capping

[0115] KH-570 was added to the crude resin product, and the temperature was raised to 100℃ and reacted for 2 hours; the temperature was lowered to 60℃, and succinic anhydride was added and reacted for 5 hours.

[0116] The resin was cooled to 40°C, degassed under vacuum at -0.08 MPa for 30 min, and filtered through a 5 μm filter bag to obtain a multifunctional epoxy-acrylic hybrid resin.

[0117] The mass ratio of bisphenol A epoxy resin, hydroxyethyl acrylate, triethylamine, octadecyl methacrylate, methacryloyloxyethyltrimethylammonium chloride, chain transfer agent, azobisisobutyronitrile, KH-570, and succinic anhydride is 20:8:0.1:7:4:0.3:0.2:2.5:3.

[0118] The amount of KH-570 used is 10% of the mass of the crude resin product; the amount of succinic anhydride used is 10% of the mass of the crude resin product; propylene glycol methyl ether acetate is used as a solvent, and by adjusting the amount of propylene glycol methyl ether acetate added, the solid content of the multifunctional epoxy-acrylic hybrid resin is made to be 70±2%.

[0119] Example 1:

[0120] Under light-protected conditions, 50 kg of the epoxy-modified acrylic resin from Preparation Example 1 was mixed with 25 kg of diethylene glycol butyl ether acetate at 40°C and stirred at 500 rpm for 30 min. Then, 10 kg of azide-modified polyester, 30 kg of rutile TiO2, 5 kg of zirconium oxide brightener, and 0.5 kg of UV absorber were added, and the mixture was dispersed at 1200 rpm for 40 min. The fineness was measured using a Hergmann fineness meter, and the fineness was required to be ≤15 μm.

[0121] The product is circulated and ground three times in a sand mill until the outlet fineness is ≤5μm; 3kg of silicon microspheres are added and dispersed at 600rpm for 20min; filtered with a 5μm filter bag and then packaged to obtain the product, a high-reflectivity white oil based on the positive photosensitive mechanism.

[0122] S1, Substrate pretreatment

[0123] Volcanic ash grinding plate, brushing pressure 1.2 kgf / cm 2The etching speed was 1.8 m / min, the wear track overlap rate was 30%; chemical ultra-roughening was performed using a mixed aqueous solution of 100 mL / L H2SO4 and 50 mL / L H2O2, at a temperature of 30 °C for 90 s, with a etching depth of 1.2 μm.

[0124] S2, Coating

[0125] High-reflectivity white ink was screen-printed using a 36T screen and a squeegee with a hardness of 70° Shore.

[0126] S3, Pre-baking

[0127] The high-reflectivity white oil was continuously dried in a tunnel oven at 72°C, with a set wind speed of 1.0 m / s and a drying time of 25 min.

[0128] S4, DI exposure

[0129] The surface dose of the substrate was measured using a 405nm radiometer. The exposure parameters were set as follows: the exposure wavelength for the high-reflectivity white oil was 405nm, and the dose was 100mJ / cm². 2 Focal length compensation +15μm;

[0130] S5, Development

[0131] Tetramethylammonium hydroxide, ethylene glycol butyl ether, ammonium polyacrylate, and deionized water are mixed and sonicated for 10 minutes, then filtered to prepare a developing solution containing 1% tetramethylammonium hydroxide, 6% ethylene glycol butyl ether, and 0.5% ammonium polyacrylate by mass.

[0132] The developing solution was sprayed onto the substrate at 30±0.5℃, with a spraying pressure of 2.0 kgf / cm². 2 The nozzle angle is 30°; the developing point is checked every 30 seconds, and the process is stopped when the ink retention rate in the unexposed area reaches about 50%; after spraying with deionized water, the area is dried with nitrogen at 40°C.

[0133] S6, Post-curing

[0134] The substrate was subjected to step curing, with the program set as follows: heating to 80°C at a heating rate of 5°C / min and curing for 20 min; heating to 100°C at a heating rate of 3°C / min and curing for 30 min; and heating to 150°C at a heating rate of 2°C / min and curing for 60 min.

[0135] After curing, a printed circuit board with high-reflectivity white oil based on positive photosensitive mechanism is obtained.

[0136] Example 2:

[0137] The preparation method is the same as in Example 1, but the film-forming resin is 52.5 kg of epoxy-modified acrylic resin; the photosensitive system is 11 kg of azide-modified polyester; the pigment system is 32.5 kg of rutile TiO2 and 4 kg of zirconium oxide brightener; the dispersion medium is 30 kg of diethylene glycol butyl ether acetate; and the functional additives are 0.75 kg of ultraviolet absorber and 2.5 kg of silica microspheres.

[0138] Example 3:

[0139] The preparation method is the same as in Example 1, but the film-forming resin is 55 kg of epoxy-modified acrylic resin; the photosensitive system is 12 kg of azide-modified polyester; the pigment system is 30 kg of rutile TiO2 and 5 kg of zirconium oxide brightener; the dispersion medium is 35 kg of diethylene glycol butyl ether acetate; and the functional additives are 0.5 kg of ultraviolet absorber and 2 kg of silica microspheres.

[0140] Example 4:

[0141] Under light-protected conditions, 50 kg of the multifunctional epoxy-acrylic hybrid resin obtained in Preparation Example 2 was mixed with 35 kg of propylene glycol methyl ether acetate and cyclohexanone at a volume ratio of 7:3. The mixture was stirred at 500 rpm for 30 min at 40 °C. Then, 10 kg of o-naphthoquinone diazide sulfonate, 20 kg of nano carbon black, 5 kg of silica matting agent, 0.1 kg of fluorocarbon leveling agent, and 1 kg of silane coupling agent were added and dispersed at 1200 rpm for 40 min. The fineness was measured using a Hergmann fineness meter, and the fineness was required to be ≤15 μm.

[0142] The sand mill is used for three cycles of grinding until the outlet fineness is ≤5μm; the product is then filtered with a 5μm filter bag and packaged to obtain a black matte ink based on a positive photosensitive mechanism.

[0143] S1, Substrate pretreatment

[0144] Volcanic ash grinding plate, brushing pressure 1.4 kgf / cm 2 The etching speed was 1.8 m / min, the wear track overlap rate was 30%; chemical ultra-roughening was performed using a mixed aqueous solution of 100 mL / L H2SO4 and 50 mL / L H2O2, at a temperature of 30 °C for 90 s, with a etching depth of 1.3 μm.

[0145] S2, Coating

[0146] The curtain is coated with matte black ink, with a slit width of 0.15 mm and a flow rate of 8 mL / min;

[0147] S3, Pre-baking

[0148] The black matte ink is pre-baked in stages. The first stage is hot air circulation at 70℃ for 5 minutes; the second stage is infrared heating at 80℃ for 10 minutes.

[0149] S4, DI exposure

[0150] The surface dose of the substrate was measured using a 365nm radiometer. The exposure parameters were set as follows: exposure wavelength of 365nm for black matte ink and dose of 65mJ / cm. 2 Focal length compensation +10μm;

[0151] S5, Development

[0152] Tetramethylammonium hydroxide, ethylene glycol butyl ether, ammonium polyacrylate, and deionized water are mixed and sonicated for 10 minutes, then filtered to prepare a developing solution containing 1% tetramethylammonium hydroxide, 6% ethylene glycol butyl ether, and 0.5% ammonium polyacrylate by mass.

[0153] The developing solution was sprayed onto the substrate at 30±0.5℃, with a spraying pressure of 2.0 kgf / cm². 2 The nozzle angle is 30°; the developing point is checked every 30 seconds, and the process is stopped when the ink retention rate in the unexposed area reaches about 50%; after spraying with deionized water, the area is dried with nitrogen at 40°C.

[0154] S6, Post-curing

[0155] The substrate was subjected to step curing, with the program set as follows: heating to 80°C at a heating rate of 5°C / min and curing for 20 min; heating to 100°C at a heating rate of 3°C / min and curing for 30 min; and heating to 150°C at a heating rate of 2°C / min and curing for 60 min.

[0156] After curing, a printed circuit board with black matte ink based on positive photosensitive mechanism is obtained.

[0157] Example 5:

[0158] The preparation method is the same as in Example 4, but the film-forming resin is 47.5 kg of multifunctional epoxy-acrylic hybrid resin; the photosensitizing system is 9 kg of o-naphthoquinone diazide sulfonate; the pigment system is 21 kg of nano carbon black and 6.5 kg of silica matting agent; the dispersion medium is 30 kg of propylene glycol methyl ether acetate / cyclohexanone with a volume ratio of 7:3; and the functional additives are 0.2 kg of fluorocarbon leveling agent and 0.75 kg of silane coupling agent.

[0159] Example 6:

[0160] The preparation method is the same as in Example 4, but the film-forming resin is 45 kg of multifunctional epoxy-acrylic hybrid resin; the photosensitizing system is 8 kg of o-naphthoquinone diazide sulfonate; the pigment system is 22 kg of nano carbon black and 8 kg of silica matting agent; the dispersion medium is 25 kg of propylene glycol methyl ether acetate / cyclohexanone with a volume ratio of 7:3; and the functional additives are 0.3 kg of fluorocarbon leveling agent and 0.5 kg of silane coupling agent.

[0161] Example 7:

[0162] Under light-protected conditions, 48 ​​kg of the multifunctional epoxy-acrylic hybrid resin obtained in Preparation Example 2 was mixed with 25 kg of propylene glycol methyl ether acetate at 40°C and stirred at 500 rpm for 30 min. Then, 9 kg of o-naphthoquinone diazide sulfonate, 21 kg of phthalocyanine green G, 6.5 kg of titanium yellow, and 0.2 kg of fluorocarbon leveling agent were added and dispersed at 1200 rpm for 40 min. The fineness was measured using a Hergmann fineness meter and was required to be ≤15 μm.

[0163] The sand mill is used for three cycles of grinding until the outlet fineness is ≤5μm; the product is then filtered with a 5μm filter bag and packaged to obtain a green ink based on positive photosensitive mechanism.

[0164] S1, Substrate pretreatment

[0165] Volcanic ash grinding plates, brushing pressure 1.2-1.5 kgf / cm² 2 The etching speed was 1.8 m / min, the wear track overlap rate was 30%; chemical ultra-roughening was performed using a mixed aqueous solution of 100 mL / L H2SO4 and 50 mL / L H2O2, at a temperature of 30 °C for 90 s, with a micro-etching depth of approximately 1.2 μm.

[0166] S2, Coating

[0167] The curtain is coated with green ink, the slit width is 0.15 mm, and the flow rate is 8 mL / min;

[0168] S3, Pre-baking

[0169] The green ink is pre-baked in stages. The first stage is hot air circulation at 70℃ for 5 minutes; the second stage is infrared heating at 80℃ for 10 minutes.

[0170] S4, DI exposure

[0171] The surface dose of the substrate was measured using a 365nm / 405nm radiometer. The exposure parameters were set as follows: the exposure wavelength for the green ink was 365nm, and the dose was 80mJ / cm². 2 Focal length compensation +12μm;

[0172] S5, Development

[0173] Tetramethylammonium hydroxide, ethylene glycol butyl ether, ammonium polyacrylate, and deionized water are mixed and sonicated for 10 minutes, then filtered to prepare a developing solution containing 1% tetramethylammonium hydroxide, 6% ethylene glycol butyl ether, and 0.5% ammonium polyacrylate by mass.

[0174] The developing solution was sprayed onto the substrate at 30±0.5℃, with a spraying pressure of 2.0 kgf / cm². 2 The nozzle angle is 30°; the developing point is checked every 30 seconds, and the process is stopped when the ink retention rate in the unexposed area reaches about 50%; after spraying with deionized water, the area is dried with nitrogen at 40°C.

[0175] S6, Post-curing

[0176] The substrate was subjected to step curing, with the program set as follows: heating to 80°C at a heating rate of 5°C / min and curing for 20 min; heating to 100°C at a heating rate of 3°C / min and curing for 30 min; and heating to 150°C at a heating rate of 2°C / min and curing for 60 min.

[0177] After curing, a printed circuit board with green ink based on positive photosensitive mechanism is obtained.

[0178] Example 8:

[0179] The film-forming resin is 50 kg of multifunctional epoxy-acrylic hybrid resin; the photosensitive system is 10 kg of o-naphthoquinone diazide sulfonate; the pigment system is 16.5 kg of phthalocyanine green G and 2.5 kg of titanium yellow; the dispersion medium is 30 kg of propylene glycol methyl ether acetate; and the functional additive is 0.3 kg of fluorocarbon leveling agent.

[0180] Example 9:

[0181] The film-forming resin is 52 kg of multifunctional epoxy-acrylic hybrid resin; the photosensitive system is 11 kg of o-naphthoquinone diazide sulfonate; the pigment system is 18 kg of phthalocyanine green G and 2 kg of titanium yellow; the dispersion medium is 35 kg of propylene glycol methyl ether acetate; and the functional additive is 0.2 kg of fluorocarbon leveling agent.

[0182] Based on this, the following design was also created:

[0183] Comparative Example 1: The formulation and experimental method were the same as in Example 2, but less epoxy-modified acrylic resin was added (10 kg);

[0184] Comparative Example 2: The formulation and experimental method were the same as in Example 2, but an excess of epoxy-modified acrylic resin (100 kg) was added;

[0185] Comparative Example 3: The formulation and experimental method were the same as in Example 4, but the amount of multifunctional epoxy-acrylic hybrid resin added was less than 10 kg.

[0186] Comparative Example 4: The formulation and experimental method were the same as in Example 4, but an excess of multifunctional epoxy-acrylic hybrid resin (100 kg) was added;

[0187] Comparative Example 5: The formulation and experimental method were the same as in Example 7, but the amount of multifunctional epoxy-acrylic hybrid resin added was less than 10 kg.

[0188] Comparative Example 6: The formulation and experimental method were the same as in Example 7, but an excess of multifunctional epoxy-acrylic hybrid resin (100 kg) was added;

[0189] The reflectance (R%), yellowing index (Δb*), development latitude, photosensitivity, resolution, and heat resistance of the ink system of this invention were tested according to the standards IEC 61947 / JIS K 5600, ASTM D2244, IPC-SM-840, ISO 28037, IPC-4781, and IPC-TM-650 2.6.8. The corresponding results are shown in Table 2 below.

[0190] Table 2. Performance test data of the reversal ink system

[0191]

[0192] By comparing Example 2, Comparative Example 1, and Comparative Example 2, it can be seen that for high-reflectivity white oil, insufficient addition of film-forming resin will lead to pigment exposure and reduced scattering efficiency; lack of antioxidant groups will exacerbate thermo-oxidative aging; the film layer will be too thin, the degree of crosslinking will decrease, the developer will penetrate excessively, and the thermal decomposition temperature will decrease.

[0193] When there is an excess of resin, the pigment is completely encapsulated, resulting in reduced light diffusion; abnormal cross-linking density causes internal stress yellowing and hinders the diffusion of the developer, resulting in a light shielding effect and insufficient edge curing.

[0194] By comparing Example 5, Comparative Example 3, and Comparative Example 4, it can be seen that for black matte ink, when the film-forming resin is insufficient, the nano carbon black cannot be continuously coated, the substrate is exposed to reflect light, the reflectivity soars, the basic function of black ink is completely lost, and the film layer is too thin, which is broken through by the developer, the substrate is excessively corroded, the photocrosslinking zone collapses, and the resolution drops sharply.

[0195] When there is an excess of resin, the resin layer becomes too thick, which weakens the light absorption efficiency of carbon black. Light scattering causes the edges to become blurred during curing. At the same time, cross-linking stress leads to the formation of microcracks, resulting in internal stress concentration and accelerating thermo-oxidative aging.

[0196] Comparative Examples 8, 5, and 6 show that for green ink, insufficient resin, excessively thin film thickness, superimposed reflection from the substrate, dispersion and aggregation of Phthalocyanine Green G, and direct thermal degradation of pigment during the curing stage result in a bluish hue.

[0197] When there is an excess of resin, the phthalocyanine green G pigment settles, while titanium yellow floats, causing yellow-green separation. This results in uneven color concentration, triggers light scattering, leads to curing dispersion, generates stress cracks, accelerates oxygen penetration, and damages the cured film.

[0198] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A reversal ink system based on positive photosensitive mechanism, characterized in that, High-reflectivity white oil is made from the following raw materials in parts by weight: Film-forming resin: 50-55 parts of epoxy-modified acrylic resin; Photosensitive system: 10-12 parts of azidolated polyester; Pigment system: 30-35 parts rutile TiO2, 3-5 parts zirconium oxide brightener; Dispersion medium: 25-35 parts of diethylene glycol butyl ether acetate; Functional additives: 0.5-1 parts of ultraviolet absorber, 2-3 parts of silica microspheres; The preparation process of the epoxy-modified acrylic resin includes the following steps: 1) Synthesis of prepolymer solution Add propylene glycol methyl ether acetate solvent to the reactor, purge with nitrogen to replace oxygen, heat to 80°C, and start stirring at 100 rpm. A monomer mixture was obtained by mixing methyl methacrylate, acrylic acid, phosphate monomer, hydroxyethyl acrylate, and 2-hydroxy-4-(3-methacryloyloxypropoxy)benzophenone. Azobisisobutyronitrile (AIBN) was dissolved in propylene glycol methyl ether acetate to obtain an AIBN solution. Slowly add monomer mixture and AIBN solution to the reactor, keep warm at 80°C for 2 hours, add more AIBN solution, cool to 70°C to obtain prepolymer solution; 2) Epoxy ring-opening grafting Add bis((3,4-epoxycyclohexyl)methyl)adipate, triphenylphosphine, and phenyl glycidyl ether, heat to 85±1℃, adjust the stirring speed to 80rpm, react for 4h, cool to 60℃, add propylene glycol methyl ether acetate to dilute, terminate the reaction, and obtain the crude product of epoxy-modified acrylic resin. 3) Post-processing Add antioxidants, stir at 60℃ for 40 min until completely dissolved, remove volatile monomers under -0.09MPa vacuum at 80℃, and stop stirring when the distillate is <0.5kg / h; After cooling to 40℃ and filtering through a 5μm filter bag, a slightly yellow, transparent, viscous liquid with a solid content of 60±2% is obtained, which is epoxy-modified acrylic resin.

2. The reversal ink system based on positive photosensitive mechanism according to claim 1, characterized in that, The ultraviolet absorber is a benzotriazole ultraviolet absorber; the zirconium oxide brightener has particle sizes of 0.2 μm and 1 μm, and the mass ratio of the two particle sizes is 1:

1.

3. The reversal ink system based on positive photosensitive mechanism according to claim 1, characterized in that, In step 1), the mass ratio of methyl methacrylate, acrylic acid, phosphate monomer, hydroxyethyl acrylate, and 2-hydroxy-4-(3-methacryloyloxypropoxy)benzophenone is 46:4.5:1.8:18:2.

7. The mass ratio of monomer mixture, bis((3,4-epoxycyclohexyl)methyl)adipate, triphenylphosphine, and phenyl glycidyl ether is 73:15:0.15:5; the amount of azobisisobutyronitrile is 1% of the mass of monomer mixture. In step 2), the propylene glycol methyl ether acetate used for dilution is 20% of the total amount of reactants; In step 3), the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1, and the amount used is 1% of the mass of the epoxy-modified acrylic resin crude product.

4. A reversal ink system based on positive photosensitive mechanism, characterized in that, Black matte ink is made from the following raw materials in parts by weight: Film-forming resin: 45-50 parts of multifunctional epoxy-acrylic hybrid resin; Photosensitizing system: 8-10 parts of o-naphthoquinone diazidesulfonate; Pigment system: 25-30 parts nano carbon black, 5-8 parts silica matting agent; Dispersion medium: a mixture of 25-35 parts of propylene glycol methyl ether acetate and cyclohexanone in a volume ratio of 7:3; Functional additives: 0.1-0.3 parts of fluorocarbon leveling agent, 0.5-1 parts of silane coupling agent; The preparation process of the multifunctional epoxy-acrylic hybrid resin includes the following steps: ① Synthesis of crude resin products Add bisphenol A epoxy resin and propylene glycol methyl ether acetate to the reactor, heat to 90°C, and stir at 150 rpm to dissolve. Hydroxyethyl acrylate and triethylamine were added dropwise at a flow rate of 1.5 L / h and reacted at 90 ± 2 °C for 3 h. Cool to 70℃, add octadecyl methacrylate, methacryloxyethyltrimethylammonium chloride, chain transfer agent, and propylene glycol methyl ether acetate. Purge with nitrogen for 30 minutes to remove oxygen. Prepare a solution of azobisisobutyronitrile and propylene glycol methyl ether acetate and add it to the reaction vessel. Heat to 80℃ and react for 4 hours to obtain crude resin product. ② Post-treatment after anhydride end-capping KH-570 was added to the crude resin product, and the temperature was raised to 100℃ and reacted for 2 hours; the temperature was lowered to 60℃, and succinic anhydride was added and reacted for 5 hours. The resin was cooled to 40°C, degassed under vacuum at -0.08 MPa for 30 min, and filtered through a 5 μm filter bag to obtain a multifunctional epoxy-acrylic hybrid resin.

5. The reversal ink system based on positive photosensitive mechanism according to claim 4, characterized in that, In ①, the mass ratio of bisphenol A epoxy resin, hydroxyethyl acrylate, triethylamine, octadecyl methacrylate, methacryloxyethyltrimethylammonium chloride, chain transfer agent, and azobisisobutyronitrile is 20:8:0.1:7:4:0.3:0.

2. In step ②, the amount of KH-570 used is 10% of the mass of the crude resin product; the amount of succinic anhydride used is 10% of the mass of the crude resin product. Using propylene glycol methyl ether acetate as a solvent, the solid content of the multifunctional epoxy-acrylic hybrid resin is adjusted to 70±2% by adjusting the amount of propylene glycol methyl ether acetate added.

6. A reversal ink system based on positive photosensitive mechanism, characterized in that, Green ink is made from the following raw materials in parts by weight: 48-52 parts of film-forming resin: multifunctional epoxy-acrylic hybrid resin; 9-11 parts of the photosensitizing system: o-naphthoquinone diazidesulfonate; A pigment system of 17-21 parts: 15-18 parts Phthalocyanine Green G, 2-3 parts Titanium Yellow; 25-35 parts of dispersion medium: propylene glycol methyl ether acetate; 0.2-0.4 parts of functional additives: fluorocarbon leveling agent.

7. The method for preparing the reversal ink system based on positive photosensitive mechanism according to any one of claims 1-6, characterized in that, Includes the following steps: Under light-protected conditions, the film-forming resin was mixed with the dispersion system at 40°C and stirred at 500 rpm for 30 min; the pigment system, photosensitizing system and functional additives were added and dispersed at 1200 rpm for 40 min; the fineness was tested using a Hergmann fineness meter, and the fineness was required to be ≤15 μm to obtain the resin mixture; The resin mixture is circulated and milled three times using a sand mill until the outlet fineness is ≤5μm; black oil or green oil is obtained. After grinding, silica microspheres were added to the resin mixture to obtain white oil; The product is obtained by filtering with a 5μm filter bag and then packaging.

8. The inverted ink system based on positive photosensitive mechanism as described in any one of claims 1-6 is applied to the solder mask process of high-density PCBs for miniLEDs / microLEDs, characterized in that, Includes the following steps: S1, Substrate pretreatment Volcanic ash grinding plates, brushing pressure 1.2-1.5 kgf / cm² 2 The etching speed was 1.8 m / min, the wear track overlap rate was 30%; chemical ultra-roughening was performed using a mixed aqueous solution of 100 mL / L H2SO4 and 50 mL / L H2O2, at a temperature of 30 °C for 90 s, with a micro-etching depth of approximately 1.2 μm. S2, Coating The curtain is coated with matte black ink or green ink, with a slit width of 0.15 mm and a flow rate of 8 mL / min; high-reflectivity white ink is screen-printed using a 36T screen and a squeegee with a hardness of 70° Shore. S3, Pre-baking Black matte ink or green ink is pre-baked in stages. The first stage is hot air circulation at 70°C for 5 minutes. The second stage involves infrared heating at 80℃ for 10 minutes; the high-reflectivity white oil is continuously dried in a tunnel oven at 72℃, with a set wind speed of 1.0 m / s for 25 minutes. S4, DI exposure The surface dose of the substrate was measured using a 365nm / 405nm radiometer. The exposure parameters were set as follows: the exposure wavelength for the high-reflectivity white oil was 405nm, and the dose was 100mJ / cm². 2 Focal length compensation +15μm; exposure wavelength of black matte ink is 365nm, dose is 65mJ / cm. 2 Focal length compensation +10μm; exposure wavelength of green ink is 365nm, dosage is 80mJ / cm. 2 Focal length compensation +12μm; S5, Development The developing solution was sprayed onto the substrate at 30±0.5℃, with a spraying pressure of 2.0 kgf / cm². 2 The nozzle angle is 30°; the developing point is checked every 30 seconds, and the process is stopped when the ink retention rate in the unexposed area reaches about 50%; after spraying with deionized water, the area is dried with nitrogen at 40°C. S6, Post-curing The substrate was subjected to step curing, with the program set as follows: heating to 80°C at a heating rate of 5°C / min and curing for 20 min; heating to 100°C at a heating rate of 3°C / min and curing for 30 min; and heating to 150°C at a heating rate of 2°C / min and curing for 60 min. After curing, a printed circuit board protected by the reverse ink system is obtained.

9. The application of the reversal ink system based on positive photosensitive mechanism according to claim 8, characterized in that, The method for preparing the developer is as follows: Tetramethylammonium hydroxide, ethylene glycol butyl ether, ammonium polyacrylate, and deionized water were mixed and sonicated for 10 minutes, then filtered to prepare a developing solution containing 1% tetramethylammonium hydroxide, 6% ethylene glycol butyl ether, and 0.5% ammonium polyacrylate by mass.

Citation Information

Cited By

  • High-temperature-resistant non-discoloring polyarylene ether nitrile modified ink and preparation method thereof

    CN121895805A